Wheelchair Tai Chi Ball Exercise for Improving Neuromuscular Functions of Older Adults With Disability - Liao, Ting; Ke, Xiong-Wen; Wang, Yong Tai (Frontiers in Aging Neuroscience, 2022)
The purposes of this perspective article were to summarize Wheelchair or Seated Tai Chi studies related to neuromuscular functions of older adults with disability; to describe the development of Wheelchair Tai Chi Ball (WTCB) exercise — a concept to combine mind-body exercise with strength training; and to propose a new Telehealth WTCB exercise for improving neuromuscular functions of old adults with spinal cord injury (SCI) and disability. With reference to neuromuscular functions, WTC intervention may have positive effects on simple reaction time, range of motion at the shoulder and trunk, static and dynamic sitting balance, handgrip strength, vagal activity, and sympathetic activity among older adults with disability. The developed WTCB intervention is a feasible and safe exercise which combines the mind-body exercise and strength conditioning into one exercise which possesses aerobic, stretching and strength trainings and may facilitate neuromuscular functions of older adults with disability. The proposed Telehealth WTCB 12 forms (TWTCB12) exercise with a “Moving Shadow” method in the telehealth may enable the learner to superimpose learner’s image on an expert’s demonstrating model to enhance the learning and practice effects. Since wheelchair users will learn and practice TWTCB12 movements in a seated position or sitting on a wheelchair the “Moving shadow” method on Zoom would provide an ideal telehealth learning and practice environment for the wheelchair users to learn and practice TWTCB12 exercise from home more feasible and user friendly.